2023
DOI: 10.1002/erv.3020
|View full text |Cite
|
Sign up to set email alerts
|

Pain experience in eating disorders: The mediating role of depression, alexithymia and interoceptive awareness

Gilda Fazia,
Elvira Anna Carbone,
Marianna Rania
et al.

Abstract: ObjectiveEvidence suggests reduced sensitivity to pain due to high pain threshold in anorexia and bulimia nervosa and a possible role of depression, alexithymia and interoceptive awareness on pain experience. This study examined whether self‐report and real‐time evoked pain experience were mediated by depression, alexithymia and interoceptive awareness in a comprehensive sample of patients with eating disorders (ED).Method145 participants (90 ED, 55 healthy controls (HC)) underwent a real‐time evoked examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 98 publications
1
0
0
Order By: Relevance
“…Moreover, we found that females showed more relevant alexithymic traits than males (as detected by the TAS-20), especially in the domain of an inadequate identification of feelings. This finding is partially in line with the literature and could be explained with the more frequent occurrence of eating spectrum traits in females than in males: the 'psychopathological core' of alexithymia is characterized by a marked difficulty in emotions' identification and elaboration and by a significant interference with self-regulation processes predisposing to dysfunctional eating behaviors, such as binge-eating [38][39][40] or emotional eating [41]. However, several studies pointed out that alexithymic traits might be more frequent among males than females as a consequence of the so-called 'normative male alexithymia' [42], characterized by a deficit in processing emotions.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, we found that females showed more relevant alexithymic traits than males (as detected by the TAS-20), especially in the domain of an inadequate identification of feelings. This finding is partially in line with the literature and could be explained with the more frequent occurrence of eating spectrum traits in females than in males: the 'psychopathological core' of alexithymia is characterized by a marked difficulty in emotions' identification and elaboration and by a significant interference with self-regulation processes predisposing to dysfunctional eating behaviors, such as binge-eating [38][39][40] or emotional eating [41]. However, several studies pointed out that alexithymic traits might be more frequent among males than females as a consequence of the so-called 'normative male alexithymia' [42], characterized by a deficit in processing emotions.…”
Section: Discussionsupporting
confidence: 87%
“…A novel study by Fazia et al (2024) investigated how depression, IA, and alexithymia mediate the relationship between ED and pain perception. The study found that individuals with EDs exhibited reduced pain sensitivity compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…The study found that individuals with EDs exhibited reduced pain sensitivity compared to healthy controls. Notably, it highlighted the role of depressive symptoms, either independently associated with alexithymia (i.e., depression is associated with an increased likelihood of perceiving greater pain) or a marked reduction in IA among those with EDs, indicating that depression may compromise IA ( Fazia et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients grappling with CP encounter heightened difficulties in regulating emotion., These are often accompanied by associated physical ailments ( La Touche et al, 2021 ). Research indicates that elevated levels of alexithymia are linked to various adverse outcomes in individuals with CP, including somatization ( Lanzara et al, 2020 ), diminished quality of life ( Tesio et al, 2018 ), psychological distress ( Ghiggia et al, 2022 ), sexual dysfunction ( Aboussouan et al, 2021 ), eating disorders ( Fazia et al, 2024 ), increased pain intensity ( Aaron et al, 2019b ), pain catastrophizing ( Shim et al, 2018 ), anger ( Di Tella et al, 2018 ), and post-traumatic stress disorder ( Fang and Chung, 2023 ).…”
Section: Introductionmentioning
confidence: 99%